Study of intrauterine fetal death cases in a tertiary care center - Meena, Lalita; Gupta, Ritu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The death of a fetus is a tragic event not only for the parents but also a great cause of stress for the caregiver. It is thus vital to identify specific probable causes of fetal death to determine the risk of recurrence, prevention or corrective action. Methods: This retrospective observational study was carried out in department of obstetrics and gynaecology, Jhalawar Medical College, Jhalawar, from July 2019 to October 2019. Intrauterine fetal death was confirmed either with ultrasound or on clinical examination. The details of complaints, obstetrics history, examination findings, mode of delivery, fetal outcomes and investigation reports were recorded. Results: A total of 114 intrauterine fetal deaths were reported amongst 2982 deliveries conducted during the study period. The incidence rate of IUFD was 38.22/1000 live births. 85.96% deliveries were unbooked. 59.64% belonged to rural population. 59.64% fetal deaths occurred in women between 20 to 25 years of age. 45.61% women were primigravida. 41.2% IUFD occurred between 26 to 31 weeks of gestation. Among the identifiable cause’s hypertensive disorders (23.68) and placental causes (19.29%) were most common. Conclusions: Unexplained causes, PIH and abruptio placentae were major causes of IUFD. Majority of fetal wastage can be prevented with universal and improved antenatal care.